Respuesta :

Answer:

f(x) = -3x^2 + 10x + 3

Step-by-step explanation:

(0,3) (2,11)(3,6)

Using the form ax^2 + bx + c = y

From the first set we know that c = 3

Write an equation for the last two sets

x=2; y=11

a(2^2) + b(2) + 3 = 11

4a + 2b = 11 - 3

4a + 2b = 8

simplify divide by 2

2a + b = 4

and

x=3, y=6

9a + 3b + 3 = 6

9a + 3b = 6 - 3

9a + 3b = 3

simplify divide by 3

3a + b = 1

:

Use elimination to find a

3a + b = 1

2a + b = 4

--------------subtracting eliminate b

a = -3

Find b using the equation 2a + b = 4

2(-3) + b = 4

b = 4 + 6

b = 10

:

The equation: f(x) = -3x^2 + 10x + 3